TAX REFORMS IN UZBEKISTAN'S TAX SYSTEM AND THEIR EFFECTIVENESS - Abror Akhrorovich Ibodullayev; Asrorbek Abdurashidovich Umaraliyev (Modern American Journals, 2025)
This scientific work analyzes the recent innovations and reforms in Uzbekistan’s tax system and their effectiveness in the national economy. The study examines measures being implemented to improve the tax system, support economic growth and development, and enhance its competitiveness across various sectors. Furthermore, consistent efforts are being made to increase tax revenues and strengthen the stability of the state budget. In recent years, numerous reforms and their innovative solutions have produced clear, positive outcomes and significant changes in the country’s financial landscape.
Keywords: Tax reforms, state budget, tax revenues, budget stability, digitalization, taxpayers, economic efficiency, statistical analysis, tax burden, tax policy, Uzbekistan’s economy, economic activity.